Top performers are not the most impressive when extreme performance indicates unreliability - Denrell, Jerker (National Academy of Sciences, 2012)
The relationship between performance and ability is a central concern in the social sciences: Are the most successful much more able than others, and are failures unskilled? Prior research has shown that noise and self-reinforcing dynamics make performance unpredictable and lead to a weak association between ability and performance. Here we show that the same mechanisms that generate unpredictability imply that extreme performances can be relatively uninformative about ability. As a result, the highest performers may not have the highest expected ability and should not be imitated or praised. We show that whether higher performance indicates higher ability depends on whether extreme performance could be achieved by skill or requires luck.